PERENCANAAN BAK PENGENDAPAN DAN PENAMPUNGAN AIR YANG BERASAL DARI MATA AIR DI KECAMATAN LAMALA - Sirampun, Maksi; Saparudin, Saparudin; Tunas, I Gede (Jurusan Teknik Sipil Universitas Tadulako, 2013)
District of Lamala Regency of Luwuk is the area in which shortage of water and difficulty in supplying the water needs of its population. This planning study aims to address the fresh water problem and determine the needs of fresh water , especially three villages in the District of Lamala namely village of Bonebabakal, Lomba and Poroan.The study was conducted by collecting primary data and secondary data, as well as direct observation in the field. Furthermore, to drain the water from the spring water to the deposition basin of 20m3 and reservoir basin of 50m3 at a service area with a distance of 3 km from the source and height difference of 128 meters can utilize the force of gravity. From the research, the spring discharge data obtained at 20.1 liters / sec and to meet the needs of local water services up to year 2031 the population projection can be calculated using the arithmetic and geometric methods.As a suggestion to optimize the volume of water , it should be made on the fresh water catchers building in the location of water springs as well as the manufacture of bags to drain the sediment sludge coming from the spring. Keywords: depositional basin, reservoir, springs